New method for selective recovery of manganese from NCM-based cathode material of spent Li-ion batteries. Issue 3 (4th July 2022) - Kim, Eunyoung; Ahn, Taebum; Kim, Tae-Young
ABSTRACT: This study provides a new leaching method for selective recovery of manganese from the spent NCM-based cathode active material of lithium-ion secondary batteries (LIBs). The recovery method involves the use of aqueous Mn(II) phase spontaneously generated in sulfate media as a reducing agent, in which Ni(III) and Co(III) are reduced to soluble species while Mn(II) precipitates as Mn(IV) oxides simultaneously. To optimize the process, the effects of time, temperature, and acid concentration on the leaching behavior were investigated. As a result, two-step successive leaching at an optimal condition was proposed, by which the dissolution efficiency of Co and Ni reached up to 99% and ~100%, respectively while Mn leaching was restricted to 15.5%. The leaching residue mainly consisted of manganese oxide (MnO2 ), containing Mn ~40%. The amount of Mn in the residue increased to ~70% by calcinating at 650 °C, which converted its phase into Mn2 O3 and Mn3 O4 . Therefore, our two-step leaching technique will lead to the recovery of nearly all the contents of Li, Co, and Ni in addition to ~70% purity Mn as supplemental benefit from spent LIB materials without using any oxidants or reductants.